Colonic Saturated Fatty Acid Concentrations and Expression of COX-1, but not Diet, Predict Prostaglandin E2 in Normal Human Colon Tissue. (2nd October 2016) - Sidahmed, ElKhansa; Sen, Ananda; Ren, Jianwei; Patel, Arsh; Turgeon, D. Kim; Ruffin, Mack T.; Brenner, Dean E.; Djuric, Zora
ABSTRACT: Prostaglandin E2 (PGE2 ) in the colon is a pro-inflammatory mediator that is associated with increased risk of colon cancer. In this study, expression of genes in the PGE2 pathway were quantified in colon biopsies from a trial of a Mediterranean versus a Healthy Eating diet in 113 individuals at high risk for colon cancer. Colon biopsies were obtained before and after 6 months of intervention. Quantitative, real-time PCR was used to measure mRNA expression of prostaglandin H synthases (PTGS1 and 2), prostaglandin E synthases (PTGES1 and 3), prostaglandin dehydrogenase (HPGD), and PGE2 receptors (PTGER2, PTGER4). The most highly expressed genes were HPGD and PTGS1. In multivariate linear regression models of baseline data, both colon saturated fatty acid concentrations and PTGS1 expression were significant, positive predictors of colon PGE2 concentrations after controlling for nonsteroidal anti-inflammatory drug use, gender, age, and smoking status. The effects of dietary intervention on gene expression were minimal with small increases in expression noted for PTGES3 in both arms and in PTGER4 in the Mediterranean arm. These results indicate that short-term dietary change had little effect on enzymes in the prostaglandin pathway in the colon and other factors, such as differences in fatty acid metabolism, might be more influential.